Compressive deformation of polycrystalline Ni-Mn-Ga alloys near chemical ordering transition temperature. (15th March 2018) - Wei, L.S.; Zhang, X.X.; Qian, M.F.; Martin, P.G.; Geng, L.; Scott, T.B.; Peng, H.X.
Abstract: Ferromagnetic shape memory Ni-Mn-Ga alloys exhibit an ordered L21 to partially ordered B2 transition at temperatures 873–1073 K. Based on the isothermal compressive results, it is demonstrated that L21 phase was brittle near ordering temperature, but the B2 phase was excellent above the chemical ordering temperature. In the compressive mode at temperatures of 473–1273 K and strain rates of 0.001–1 s −1, the plastic deformation mechanism was found to be strongly dependent on the Zener-Hollomon parameter Z : the dynamic recrystallization was the dominant mechanism at the low Z region in the B2 state, then with increasing Z the dynamic recovery and ordering transition from B2 to L21 occurred, finally only dynamic recovery existed at the high Z region in the L21 state. Based on the processing map constructed from the isothermal compressive curves, hot extrusion of Ni-Mn-Ga alloy with ratio as high as 9:1 was achieved at 1273 K. This proved that polycrystalline Ni-Mn-Ga alloys are strikingly facile for large plastic deformation in the B2 state by dynamic recrystallization at temperatures around 1273 K and strain rate 0.03 s −1, which affords a viable temperature and strain rate processing window for this intrinsically brittle alloy. Graphical abstract: Unlabelled Image Highlights: Plasticity in a Ni51.3 Mn27.6 Ga21.1 alloy was demonstrated over L21 → B2 transition temperatures. DRV process occurred around the L21 → B2 transition temperature range. DRX and DRV/DRX mixed processes existed in B2 phase. Partially ordered crystal structure and DRX contributed to the good plasticity of B2 phase.